Diterpenoid alkaloids from a Tibetan medicinal plant Aconitum richardsonianum var. pseudosessiliflorum and their cytotoxic activity - Yang-Qing He; Bing-Hua Yao; Zhan-Ying Ma (Elsevier, 2011)
The chemical constituents from Aconitum richardsonianum var. pseudosessiliflorum were investigated. The roots of this plant were extracted three times with 90% EtOH at the room temperature. The ethanol extracts were combined and concentrated under reduced pressure to yield residue, which was suspended in water and successively partitioned with chloroform. The chloroform extraction was isolated and purified by silica gel and Sephadex LH-20 column chromatography. Six compounds were isolated and elucidated as delelatine (1), isodelpheline (2), 3-acetylaconitine (3), isoatisine (4), nordhagenine A (5) and yunaconitine (6). Compounds 1â5 were obtained from Aconitum Brunneum for the first time. Compound (1) showed significant cytotoxic activities (IC50=Â 4.36Â Î¼M) against the human tumor cell line P388. Keywords: Aconitum richardsonianum var. pseudosessiliflorum, Ranunculaceae, diterpene alkaloids, cytotoxic activity